2023
DOI: 10.3389/fped.2022.1066367
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in infants with severe bronchopulmonary dysplasia: A review

Abstract: In recent years, with increased survival of infants with severe bronchopulmonary dysplasia (BPD), long term ventilation due to severe BPD has increased and become the most common indication for tracheostomy in infants less than one year of age. Evidence shows that tracheostomy in severe BPD may improve short- and long-term respiratory and neurodevelopmental outcomes. However, there is significant variation among centers in the indication, timing, intensive care management, and follow-up care after hospital dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies 9 . In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies 9 . In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement.…”
Section: Discussionsupporting
confidence: 87%
“…37,[43][44][45][46][47] This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies. 9 In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement. BPD in a multicenter study; 23 there was no racial difference in probability of tracheostomy placements in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,[43][44][45][46][47] This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies. 9 In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement. In our adjusted analyses, children of non-White, non-Black race had a nearly threefold higher risk of 3-year mortality across predictor groups as compared with white peers; notably, the other covariates of sex, insurance type, and CCCs included in this model did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%